PENGARUH JUMLAH KREDIT, NPL, BOPO, DAN LIKUIDITAS TERHADAP PROFITABILITAS (Students' Journal of Accounting and Banking, 2012)
This research was conducted to test the effect of the amount of credit given, Non were Perfoming Loan (NPL), the level of Liquidity, BOPO diproksikan through Loan Deposit Ratio (LDR) towards profitability through diproksikan Return on Assets (ROA) on banking companies listed on the Indonesia stock exchange in 2008-2009.Population employed in this research is the entire banking company listed on the stock exchange in Indonesia during the years 2008-2010. In this study, researchers used a purposive sampling so obtained 24 companies that meet the criteria. The data type used is secondary data that is derived from the financial statements are published and available through the official website of the Indonesia stock exchange. Methods of analysis used is Regression with significance level of 5%.From the results of testing done to this research revealed that the number of simultaneous credit given, and are not significantly influential LDR. While Non were Perfoming Loan (NPL) and influential BOPO significantly. Being of partial test results, obtained that the amount of credit given influential positive and not significant. For NPL and BOPO negatively and significant. As for LDR and insignificant negatively against ROA.Keywords: The Amount of Credit Given, NPL, BOPO, LDR, ROA